Banished Men How Migrants Endure the Violence of Deportation - Andrews, Abigail Leslie (University of California Press, 2023)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more . What becomes of men the U.S. locks up and kicks out? From 2009 to 2020, the U.S. deported more than five million people-over 90 percent of them men. In Banished Men, Abigail Andrews and her students tell 186 of their stories. How, they ask, does expulsion shape men's lives and sense of themselves? The book uncovers a harrowing carceral system that weaves together policing, prison, detention, removal, and border militarization to undermine migrants as men. Guards and gangs beat them down, till they feel like cockroaches, pigs, or dogs. Many lose ties with family. They do not go "home." Instead, they end up in limbo: stripped of their very humanity. Against the odds, they fight for new ways to belong. At once devastating and humane, Banished Men offers a clear-eyed critique of the violence of deportation.